Access, excess, and ethics—towards a sustainable distribution model for antibiotics. (May 2014) - Heyman, Gabriel; Cars, Otto; Bejarano, Maria-Teresa; Peterson, Stefan
Abstract The increasing antibiotic resistance is a global threat to health care as we know it. Yet there is no model of distribution ready for a new antibiotic that balances access against excessive or inappropriate use in rural settings in low- and middle-income countries (LMICs) where the burden of communicable diseases is high and access to quality health care is low. Departing from a hypothetical scenario of rising antibiotic resistance among pneumococci, 11 stakeholders in the health systems of various LMICs were interviewed one-on-one to give their view on how a new effective antibiotic should be distributed to balance access against the risk of inappropriate use. Transcripts were subjected to qualitative 'framework' analysis. The analysis resulted in four main themes: Barriers to rational access to antibiotics; balancing access and excess; learning from other communicable diseases; and a system-wide intervention. The tension between access to antibiotics and rational use stems from shortcomings found in the health systems of LMICs. Constructing a sustainable yet accessible model of antibiotic distribution for LMICs is a task of health system-wide proportions, which is why we strongly suggest using systems thinking in future research on this issue.